Vibratory finishing on SLM-printed hip stem implant - Goh, Joo Hao (2019)
The primary objective of this study is to investigate the viability of utilizing vibratory finishing to post process SLM printed parts to standards desired for Ti64 hip stem implants. SLM printed parts are able to customize an implant best suited to the patient to be printed, heaping various long-term benefits. However, parts will have to be post-processed after fabrication due to the inherent unsuitable surface roughness characteristics of the parts. Vibratory finishing is one of the most popular forms of post processing. Its inherent characteristics allow it to process many parts simultaneously and automatically. This makes it one of the most cost-efficient post processing methods available. This report will utilize vibratory finishing to process the fabricated parts with 2 kinds of media and various key machine parameters being varied. Tests will then be conducted on the processed parts to understand the differences in surface quality improved by the vibratory finishing process. Hashimoto’s model will also be used in the course of the report to further evaluate the findings. It is further discovered that only certain surfaces of the built samples are able to be finished to required standards for use as hip stem implants, however this problem can be mitigated whilst designing of the hip stem implant for the patient.